Informing a USD 21.8 billion investment for scaling a solar irrigation model in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
In 2017, the Government of India committed USD 21.8 billion to the solarization of farms. The investment was informed by the piloting and evaluation of the Solar Pump Irrigators' Cooperate Enterprise (SPICE) model by IWMI and CCAFS in collaboration with Tata Trust and WLE.